Identification and characterisation of epigenetic mechanisms in osteoblast differentiation of human mesenchymal stem cells - Kramm, A (2014)
A major therapeutic challenge in musculoskeletal regenerative medicine is how to effectively replenish bone tissue lost due to pathological conditions such as fracture, osteoporosis, or rheumatoid arthritis. Mesenchymal stem cells are currently investigated for applications in bone-tissue engineering and human bone marrow-derived mesenchymal stem cells (hMSCs) could be a promising source for generation of tissue-engineered bone. However, the therapeutic potential of MSCs has not been fully exploited due to a lack of knowledge regarding the identity, nature, and differentiation of hMSCs. Epigenetic mechanisms regulating the chromatin structure as well as specific gene transcription are crucial in determination of stem cell differentiation. With the aim to systematically identify epigenetic factors that modulate MSC differentiation, the work in this thesis encompasses an approach to identify epigenetic mechanisms underlying, initiating, and promoting osteoblast differentiation, and the investigation of individual epigenetic modulators. Various osteogenic inducers were validated for differentiation of MSCs and an assay allowing assessment of differentiation outcome was developed. This assay was subsequently employed in knockdown experiments with lentiviral short hairpin RNAs and inhibitor screens with small molecules targeting putative druggable epigenetic modulator classes. This approach identified around 100 epigenetic modulator candidates involved in osteoblast differentiation, of these candidates approximately 2/3 downregulated and 1/3 upregulated alkaline phosphatase (ALP) activity. Serving as a proof-of-concept, orthogonal validation experiments employing locked nucleic acid (LNA) knockdown were performed to validate a subset of candidates. Two identified target genes were selected for further investigation. Bromodomain-containing protein 4 (BRD4) was identified as one component of epigenetic regulation; its inhibition led to a decrease in ALP expression, downregulation of key osteoblast transcription factors Runx2 and Osterix, as well as impaired bone matrix formation. Knockdown of lysine (K)-specific demethylase 1A (KDM1A/LSD1) upregulated ALP activity and treatment with a small molecule inhibitor targeting KDM1A led to an increase in ALP, RUNX2, and bone sialoprotein expression. Intriguingly, in a transgenic mouse model overexpressing Kdm1a a decrease in bone volume and bone mineral density was observed, thus supporting the hypothesis that KDM1A is a central regulator of osteoblast differentiation.